308 nm monochromatic excimer light (MEL) in dermatology [Dermatolojide 308 nm monokromatik excimer işik sistemleri] - (:unkn) unknown (My University, 2008)
"Targeted phototherapy" is a recently described therapeutic option in photodermatology. It is used to describe the phototherapy devices which can deliver high doses of ultraviolet (UV) radiation selectively to the involved skin. Several of these devices with different emission spectrums are currently in use. 308 nm monochromatic excimer light (MEL) is among these "targeted phototherapy" systems and represents one of the most important advances in phototherapy after the development of narrowband UVB. The wavelength of this new phototherapeutic option is very close to narrowband UVB. Many studies have been conducted to investigate the effectiveness of 308 nm MEL in several dermatological diseases, mainly psoriasis and vitiligo. Main advantages of MEL are protection of the healthy, uninvolved skin from excess UV radiation in patients with limited involvement and the much faster response to therapy compared with conventional phototherapies. We review in this article the properties of 308 nm MEL and discuss its current and future use in dermatology.
Keywords: Excimer; MEL; Monochromatic; Targeted phototherapy